Signature of Femininity in Diary Records by Olga Bergholz from the Years 1939–1942 - Komisaruk, Ewa (Poznańskie Studia Slawistyczne, 2016)
This article is based on the diary of a Russian poet, Olga Bergholz. Records from the years 1939–1942 are analyzed in detail. Records were developed in the period of Stalinist repression, and during the blockage of Leningrad. From a gender perspective, their reading allows situating the work of this poet in a new context. Soviet literary classic, Muse siege, eulogizing heroism of Leningrad residents, shows its second face – a face of a woman focused on everyday experience. The article analyzes notes on autothematism, love and categories of carnality.